2022
DOI: 10.32604/cmc.2022.028618
|View full text |Cite
|
Sign up to set email alerts
|

Body Worn Sensors for Health Gaming and e-Learning in Virtual Reality

Abstract: Virtual reality is an emerging field in the whole world. The problem faced by people today is that they are more indulged in indoor technology rather than outdoor activities. Hence, the proposed system introduces a fitness solution connecting virtual reality with a gaming interface so that an individual can play first-person games. The system proposed in this paper is an efficient and cost-effective solution that can entertain people along with playing outdoor games such as badminton and cricket while sitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This system could be implemented in several educational institutions, including intelligent training systems, virtual tutors, intelligent simulations, and interactive learning management methods [28]. Afsar (2022) proposed an efficient and cost-effective system that allows people to be entertained while sitting in a room playing outdoor games such as badminton and cricket, with the main goal that the person is enjoying while playing the game and engaging in physical activity [29]. performed eight minigames for cognitive assessment such as word pairs, memory scanning, and size counting in older adults, young adults, and patients with cognitive impairment, respectively, and showed that the scores obtained in the games correlated with the presence of patients' functioning, and that cognitive video games could be used to track the cognitive function of older adults with and without cognitive impairment evolution [30].…”
Section: Related Workmentioning
confidence: 99%
“…This system could be implemented in several educational institutions, including intelligent training systems, virtual tutors, intelligent simulations, and interactive learning management methods [28]. Afsar (2022) proposed an efficient and cost-effective system that allows people to be entertained while sitting in a room playing outdoor games such as badminton and cricket, with the main goal that the person is enjoying while playing the game and engaging in physical activity [29]. performed eight minigames for cognitive assessment such as word pairs, memory scanning, and size counting in older adults, young adults, and patients with cognitive impairment, respectively, and showed that the scores obtained in the games correlated with the presence of patients' functioning, and that cognitive video games could be used to track the cognitive function of older adults with and without cognitive impairment evolution [30].…”
Section: Related Workmentioning
confidence: 99%